Women in Contemporary Slovenian Diplomacy - Zupančič, Eva; Kočí, Kateřina; Madarászová, Alexandra; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
This bachelor’s thesis is dedicated to women in contemporary Slovenian diplomacy. It mainly deals with the question of where women in Slovenian diplomacy are and what the main problems and obstacles in their career path are. As diplomacy is a specific field, these problematics can also be applied to women in diplomacy on a global scale and not only to Slovenia. Special emphasis is placed on the empirical part of the thesis, which is placed side by side for comparison with the studies of the Slovenian Ministry of Foreign Affairs from 2009 and 2020. It is also interesting because both men and women are included in the research. An analysis of the questionnaires and interviews showed that quite a few changes have taken place in the last ten years and that gender equality is not as problematic as other obstacles. This bachelor’s thesis represents a good starting point for further research in the field of women in Slovenian diplomacy.
Vedoucí práce: Kateřina Kočí
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní studia - diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses